Combined Versus Sequential Injection of Mepivacaine and Ropivacaine for Supraclavicular Nerve Blocks. Issue 2 (1st February 2011) - Roberman, Dmitry; Arora, Harendra; Sessler, Daniel I.; Ritchey, Michael; You, Jing; Kumar, Priya
Abstract : Background: An ideal local anesthetic with rapid onset and prolonged duration has yet to be developed. Clinicians use mixtures of local anesthetics in an attempt to combine their advantages. We tested the hypothesis that sequential supraclavicular injection of 1.5% mepivacaine followed 90 secs later by 0.5% ropivacaine speeds onset of sensory block and prolongs duration of analgesia compared with simultaneous injection of the same 2 local anesthetics. Methods: We enrolled 103 patients undergoing surgery suitable for supraclavicular anesthesia. The primary outcome was time to 4-nerve sensory block onset in each of the 4 major nerve distributions: median, ulnar, radial, and musculocutaneous. Secondary outcomes included time to onset of first sensory block, time to complete motor block, duration of analgesia, pain scores at rest and with movement, and total opioid consumption. Outcomes were compared using the Kaplan-Meier analysis with the log-rank test or the analysis of variance, as appropriate. Results: Times to 4-nerve sensory block onset were not different between sequential and combined anesthetic administration. The time to complete motor block onset was faster in the combined group as compared with the sequential. There were not significant differences between the 2 randomized groups in other secondary outcomes, such as the time to onset of first sensory block, the duration of analgesia, the pain scores at rest or with movement, or the total opioid consumption. Conclusions: Sequential injection of 1.5% mepivacaine followed 90 secs later by 0.5% ropivacaine provides no advantage compared with simultaneous injection of the same doses.